The model “ecclesiastical institution”: the historical perspective - NACCI, MATTEO (Prawo Kanoniczne, 2018)
This work is a conference in the Faculty of Law of the University of Bari (Taranto office, Italy) that consider the historical-juridical evolution of the “ecclesiastical institution” model with respect to the welfare activity carried out by the Church and to the ecclesiastical hospital institution.